The Carrying Capacity Analysis of Rice Plants Agriculture to Fulfill Food Needs in Pati Regency - Mitha Fitria Anggraini; Eva Banowati (Geosfera Indonesia, 2022)
The fulfillment of food needs is one indicator of community welfare. The calculation of the carrying capacity of food crops is used to determine the extent to which an area meets its food needs. The aims of this study were: (1) to calculate the level of carrying capacity of rice plants in Pati Regency, (2) to plan land that has the opportunity to be used as a LP2B area, and (3) to find out the maximum population and year in Pati Regency to meet food needs. The technique of analyzing the carrying capacity of rice plants uses the calculation of the carrying capacity of natural resources and the analysis of determining land that has the potential to become sustainable food cropland using an overlay map analysis with ArcGIS. The results showed that the value of the rice plant commodity had a carrying capacity value of more than 1, which was 1,371. The results of the map-making, the land that has the opportunity to be used as permanent rice fields is 50.635 hectares. The maximum population that can be met by annual rice production is 1.622.356 people. The results of population projections using the geometric method, the maximum year Pati Regency can be self-sufficient in food is 2040. The fulfillment of sustainable food needs can be realized through monitoring the implementation of the LP2B program so that the conversion rate of agricultural land can be minimized. Keywords : Carrying Capacity; Rice Plants; Food Needs Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License